Biological record of added manganese in seawater: a new efficient tool to mark in vivo growth lines in the oyster species Crassostrea gigas - Barbin, Vincent; Ramseyer, Karl; Elfman, Mikael (International Journal of Earth Sciences, 2008)
International audience